Allelic diversity of the SSR locus VVIB23 linked to the flower sex in wild-growing grapevine genotypes of Krasnodar Territory - E. T. Ilnitskaya; M. V. Makarkina; E. A. Kozhevnikov; I. V. Gorbunov (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. Studying wild-growing grapevines is of interest because it expands the knowledge on the genetic diversity within the gene pool and helps to search for new resistance sources. One of the main differences between wild vines and cultivars is the type of their reproductive system: wild grapes are represented by cross-pollinated dioecious vines, while cultivated ones are, with rare exceptions, hermaphrodites capable of self-pollination. A DNA marker applicable to determine the grape flower sex has been identified.Materials and methods. The VVIB23 DNA marker to the Sex gene determining the flower sex was used to study 36 genotypes of wild-growing grapes selected in 2019–2021 within the Utrish Nature Reserve near Gelendzhik and the Krasny Les State Nature Reserve on the right bank of the Kuban River. PCR technique was applied, and the results were evaluated on a Nanofor 05 genetic analyzer.Results. The studied grapevine accessions were found to be variable for the VVIB23 SSR locus: 7 types of alleles were identified. Alleles corresponding to the male flower type were present in 14 genotypes, and those corresponding to the female type in 21. A PCR fragment whose size, according to the published data, correlated with hermaphroditism was not found, which is typical for wild genotypes. The DNA marker analysis failed to determine the flower sex of one accession.Conclusion. The results of the DNA marker analysis showed that the studied wild-growing grapevine genotypes were dioecious forms